Sericulture, its type and Silkworm Rearing Technologies A review - Banerjee, Nirvik; Pal Singh , Dr. Ravinder (Innovative Research Thoughts, 2017)
Sericulture also known as silk farming where the silkworms are reared to produce silk. There are varieties of silk produced all over the world. Different types of silk such as mulberry silk, non-mulberry silk, anaphe, fagara, coan, mussel, spider etc. silks. One of the rarest silk producer is- Assam that introduces three natural wild silks- golden muga, white pat and warm eri silk. This article throws an insight into the cultivation of silkworm and creation of the beautifully refined silk. It is not only considered as a tradition but also a living culture of Assam. Many cottage and small scale textile industries engages in such farm-based, labour intensive commercial economic activity providing employment to the rural farmers and attracts profit seeking entrepreneurs as it requires low investment with relatively higher returns.